Dípteros frugívoros e seus parasitoides associados à mangueira em ambiente semiárido - Santos, Wigna Gabriela Nunes (2015)
Brazil is one of the largest fruit producers in the world, however part of its production is not exported due to phytosanitary barriers imposed by importing countries. The incidence of frugivorous flies in orchards cause depreciation in fruits and serious damage to the producer, an alternative for the control of these pests, are parasitoids. The objective of this study was know to frugivorous flies and their parasitoids, associated with mango fruits in two maturity stages and the fruit of ripe guava. Mango fruits were harvested at physiological maturity stage and mature on the plant, and fruit ripe guava in the states of Rio Grande do Norte (Polo Açu-Mossoró) and Ceará. After harvest, the fruits were taken to the of laboratory of applied entomology of UFERSA, where they were weighed and placed in plastic containers containing vermiculite and closed with voile fabric. After 10 to 15 days vermiculite was sieved and pupae obtained counted and placed in Petri dishes until the emergence of adults. Also were placed traps types of McPhail and Jackson, containing hydrolyzed corn protein 5% and Trimedilure, respectively, in four orchards with products intended to export. Weekly (McPhail) and fortnightly (Jackson), the traps were monitored and insects captured sent to the laboratory. We collected 400 mango fruits and 1.331 guava fruits. The mango fruits in physiological maturity stage were not infested by any insect, since the ripe fruit on the plant were infested by C. capitata (34.4%) and Z. indianus (65.6%), the guava fruits were obtained only pupae of Z. indianus. Besides the flies were found collected figitídeos parasitoids of Z. indianus. Only, C. capitata was captured in traps and contacted that non infestation of the fruits in physiological maturity stage, for this tefritídeo is not associated with its population density in the orchard, but the inherent fruit factors